Підсумки проведення археологічних експертиз на території Миколаївської обл. у 2008—2009 рр. - Горбенко, К.В.; Смирнов, О.І.; Філатов, Д.В. (Археологічні дослідження в Україні, 2010)
The paper presents the main results of the archeological examinations conducted on the territory of Mykolayiv Oblast by the State Enterprise Scientific Research Centre «Lukomorye» in 2008—2009. It contains information on the condition of preservation and exposure of new archeological objects.